Depictions of “mental illness” in Greek criminal court rulings: Α discourse analysis - Eleni Mousourouli; Despina Neztekidou; Eugenie Georgaca (Ψυχολογία: το Περιοδικό της Ελληνικής Ψυχολογικής Εταιρείας, 2024)
The present study investigates the constructions of people diagnosed with “mental illness” in Greek criminal court rulings. A Foucauldian discourse analysis approach was applied to criminal court rulings published from 2009 to 2018 to identify dominant discursive resources used to construct “mental illness”, as well as the functions performed by judicial discourse through the specific depictions of perpetrators and their crimes. Two main constructs emerged from the analysis. When constructing the unimputable “dangerous mental patient”, an intersection of biomedical and dangerousness discourses depicts the person as unpredictable, incapable of self-awareness, self-determination, and moral judgment. In the imputable “criminal personality” construction, the impact of “mental illness” on the committed crimes is relativized, since the criminal act is attributed to psychological characteristics of the individual, who is portrayed as deliberately violating the rules of socially acceptable behavior despite being capable of rational thinking and moral reasoning. The central issues that emerged include the pre-constructed categorization of the perpetrators into imputable or non-imputable, according to the determined degree of moral agency, and the selective utilization of biomedical discourse by the court, whereby it evaluates psychiatric expertise sometimes as objective evidence and others as unreliable opinion.